Social Construction of the Power Relations of Sole Parenting of Nyai in the Solo Raya Pesantren - Rhesa Zuhriya Briyan Pratiwi; Ulfa Fauzia Argestya; Siti Fathonah (Jurnal Sosiologi Agama, 2025)
The position of women remains a sensitive topic, both within and beyond the Pesantren. This research aims to examine the social construction of the power relations of the Nyai whose Kiai has left behind. This research uses a descriptive qualitative method with snowball sampling. Data collection techniques use interviews, documentation, and observation. The subjects in this study were 4 Nyai from Singoludiro Islamic Boarding School, Al Mubarrok Islamic Boarding School in Boyolali, Qoshul Qur'an Islamic Boarding School in Klaten, and Nyai Al Muayyad Islamic Boarding School in Solo. Social construction consists of three stages. First, externalization occurred during the adjustment period following Kiai's marriage. Second, the objectification stage is carried out by considering the needs of the Pesantren. Nyai then continued Kiai's public role as a wife. It is a sign that a devoted wife must continue Kiai's struggle. The third stage of internalization occurs when Nyai is fully aware of Nyai's position as the sole caregiver in the Pesantren. The parenting pattern used by Nyai is still the same as the Pesantren criteria in providing complete care for Kiai and Nyai. What differs is that the actor caring for him is now a single actor. The connection between power relations and knowledge production is shown in various forms. It can be seen from Nyai that inherent capital, such as capital, cultural capital, and intellectual capital, can produce knowledge according to their basic abilities. This ability was developed through the production process that Nyai and Kiai underwent while living together and through the initial skills they had when managing their care in the past. The notable finding is that Nyai's parenting patterns tend to mirror those adopted from Kiai.